Isolation, Characterization, and Molecular Identification of Phosphate Solubilizing Bacteria from Several Tropical Soils - Hazra, Fahrizal; Pratiwi, Etty (UNIVERSITY OF LAMPUNG, 2013)
The objectives of the research were: (i) to isolate and characterize of phosphate solubilizing bacteria (PSB) and (ii) to identify PSB based on molecular amplification of 16S rRNA gene. Soil samples were collected from rhizosphere in Bogor, West Nusa Tenggara, and East Nusa Tenggara. Several stages in this research were: (i) isolation PSB in Pikovskaya agar, (ii) morphological and biochemical characterization of PSB, (iii) measurement of phosphatase enzymes, and (iv) measurement of secreting indole acetic acid phytohormone. As many as 29 isolates of PSB have been collected and three isolates of them, namely: P 3.5 (East Nusa Tenggara), P 6.2 (West Nusa Tenggara), and P 10.1 (Citeureup, West Java) were chosen for further study. There were many characteristics of isolate P 10.1: (i) it had capable to solubilize P with the value of highest solubilization index (1.80), (ii) it had the highest phosphatase enzyme (120.40 mg kg-1), and (iii) it had the highest pH decrease at each observation for six days. Isolates P 3.5 and P 10.1 were the Gram-negative bacteria with coccus shapes and isolate P 6.2 was a Gram-negative bacteria with bacillus shape. Deoxiribonucleat Acid (DNA) amplification of these bacteria employing 16S rRNA primers generated the 1,300bp-PCR product. The results of the analysis of 16S rRNA gene sequences showed that isolates P 3.5 and P 10.1 has 98% similarity with Gluconacetobacter sp. strains Rg1-MS-CO and isolate P 6.2 has 97% similarity with Enterobacter sp. pp9c strains.Keywords: 16S rRNA, indole acetic acid, isolation, phosphatase enzymes, phosphate solubilizing bacteria[How to Cite : Hazra F and E Pratiwi. 2013. Isolation, Characterization, and Molecular Identification of Phosphate Solubilizing Bacteria from Several Tropical Soils. J Trop Soils, 18 (1): 67-74. doi: 10.5400/jts.2013.18.1.67][Permalink/DOI: www.dx.doi.org/10.5400/jts.2013.18.1.67]